Insect Diversity and Pest Attack Intensity of Leaf Beetle (Epilachna sparsa) on Purple Eggplant (Solanum melongena L.) with the Application of Botanical Pesticides - Sopandi, Deni; Siriyah, Siti Latifatus; Laksono, Rommy Andhika; Saputro, Nurcahyo Widyo Daru (Jurnal Biologi Tropis, 2025)
The extensive use of synthetic pesticides has been shown to adversely affect ecosystems, including the diversity of insect populations. As a result, there is an increasing demand for environmentally sustainable pest control methods, such as botanical pesticides. This study aims to evaluate the diversity of insect species as well as the attack intensity of the leaf beetle (Epilachna sparsa) on purple eggplant (Solanum melongena L.) through the application of botanical pesticides. The research used a single-factor Group Random Design (RAK) with five replicates and five treatment groups: control, papaya leaf, neem leaf, a combination of papaya and neem leaves, and synthetic pesticide. Insect sampling was conducted using types of trap: pitfall traps, yellow sticky traps, and sweep nets, while the collected data were analyzed using analysis of variance, followed by a Least Significant Difference (LSD) test at the 5% significance level. The findings revealed that botanical pesticides did not have a significantly different effect on insect diversity or pest attack intensity, with the Shannon-Wiener diversity index ranging from 2.08–2.29, indicating a moderate level of diversity (1 < H’ < 3). Notably, the treatment using papaya leaf extract resulted in the lowest damage intensity by leaf beetle (E. sparsa), ranging from 15.83% to 20.83%. These results suggest that botanical pesticides, particularly papaya leaf extract, can reduce pest damage while maintaining ecological balance, as reflected in the shifts in abundance of various insect orders and their population dynamics.